Practical strategies for the modern academic library - Heery, Mike (Aslib, The Association for Information Management, 1996)
Guidance and tips on the day-to-day practicalities of providing an effective information service. Draws on `best practice' in a wide range of academic libraries. Examines keys issues in the modern academic library. Examples of user education log, library evaluation sheet and customer care statement.